TEACHERS’ PROBLEMATIC IN IMPLEMENTING THE 2013 CURRICULUM AT THE STATE SENIOR HIGH SCHOOL (SMA N) 1 TAKENGON - Candra Wijaya; Maulida Maulida; Husni Laili (State Islamic University of North Sumatra Indonesia, 2020)
This study aims to describe the teacher's problems in implementing the 2013 curriculum in SMA Negeri 1 Takengon. The research method uses descriptive qualitative. The aspects of the discussion include problems, efforts, supporting factors and obstacles in implementing the 2013 curriculum. Data collection techniques are applied through observation, interviews and documentation. The results showed that teacher problems related to time, learning media, a lot of administration had to be prepared, lack of student handbooks, difficult assessment standards especially aspects of attitude and knowledge. To overcome these problems, various efforts have been made such as: following training for teachers and students. The school provides funds; the school committee coordinates with parents. Supporting and inhibiting factors are also felt by teachers, but they continue to strive to implement the 2013 curriculum so that goals are achieved in accordance with what is expected in the 2013 curriculum. Keywords: Teachers’ Problematic, Curriculum Implementation, State Senior High School (SMA N) 1 Takengon